The moral panic about the socializing of young people in Minangkabau - Parker, Lyn (Wacana, Journal of the Humanities of Indonesia, 2014)
This paper analyses the discourse surrounding the perceived threat of free seks and pergaulan bebas (free socializing) to the moral health of young Minangkabau people, and in particular, young women, in West Sumatra. It uses the sociological frame of "moral panic" to examine contemporary discussions about globalization and the influence of "the West" in West Sumatra. The paper examines the way in which "the authorities" in West Sumatra (media, such as teen magazines and newspapers, academics, government and law, teachers, and community leaders) present the threat, and the way in which young people, who are the target of the moral panic onslaught, see themselves in relation to the threat. I argue that, unlike the original "folk devils" of the moral panics in Britain, young people in Minangkabau broadly give their consent to the authorities, displaying a striking commitment to social conservatism, local culture, and Islamic values.